Sustainable Media: Environmental Responsibility in the Industry - Arshad, Sabeen (Journal of Peace, Development and Communication, 2024)
This study explores the impact of sustainable media on dispersing relevant information and agenda-setters to interrogate the issues pertaining to ecological pollution, climate change, and loss of biological variability as they pertain to the media industry in Pakistan. It is hypothesized that sustainable media promotes and sustains the Sustainable Development Goals (SDGs) of 2030. This study structured its methodology to conform with the qualitative methodology, making its data gathering and evaluation into textual analysis. This study found that the Pakistan media has the capacity to broaden understanding of environmental issues such as climate change, pollution, and loss of biodiversity. However, this study discovered that there are limited studies available for showing the complexity and pluralistic principle needed to reinforce environmental responsibility. Sustainable media has the capacity to sustain and achieve the SDGs 2030 plan. However, there is a need for the provision of more studies on the subject.